Improving Students' Learning Outcomes On Polynomial Materials In Class XI MIPA 2 MAN Kota Singkawang Using The Group Investigation Model - Taslima, Taslima (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2022)
Based on the experience of teaching Polynomial material, many students' learning outcomes are still below the standard of completeness. One of the factors that cause it is the learning model. The purpose of this research is to improve the learning outcomes of students in class XI MIPA 2 MAN Kota Singkawang by applying the Group Investigation learning model to the Polynomial material for the 2021-2022 school year. The Group Investigation learning model is a cooperative learning model that involves students actively in learning. This research is Classroom Action Research which consists of 2 cycles, each cycle consists of 2 meetings. Data collection techniques using student learning tests. To find out changes in learning outcomes, an analysis of the test results was carried out using a paired t. The results of the study after the first cycle of the average student learning outcomes were 71.39 with learning completeness of 75%. After the second cycle, the average student learning outcomes were 81.11 with 91.67% learning completeness. From the results of the comparison of post-test cycle I with post-test cycle II, the effect size is 1.15, which means that the effectiveness is large. The results of the paired t-test obtained showed a P-value of 0.000 in the first and second cycles. This shows that there is a significant change in the results of the pre-test and post-test after the implementation of the Group Investigation model, meaning that the Group Investigation model can improve student learning outcomes.